CONSIDERING ECOLOGICALLY SUSTAINABLE PACKAGING DURING DECISION-MAKING WHILE BUYING FOOD PRODUCTS - Petljak, Kristina; Naletina, Dora; Bilogrević, Kristina (Economics of Agriculture, 2019)
Modern production of packaging is characterized by great choice of packaging materials and the shape of the packaging. There is almost no product on the market that does not have highlighted symbols that should give information about the product and the packaging. Although most consumers pay attention to the symbols, a certain number never checks them, because they consider them irrelevant. The paper investigates consumer perception of the importance of green packaging of food products. A primary research on the sample of 115 respondents has been carried out investigating respondents behaviour while making the choice on food product packaging. The findings suggest that concern for the environment and less danger for health are two major motives for buying food products in ecologically sustainable packaging. The respondents think that wood and paper have least influence on the environment, while plastic and glass harm the environment the most.